Working conditions and their effect on the health level of psychiatric staff (literature review) - A. V. Glushkova; N. V. Semenova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The range of adverse environmental factors affecting the health of psychiatrists is quite wide. It includes biological and chemical substances, emotional exhaustion and professional burnout, permanent exposure to stress factors of an aggressive environment, forced working posture, tension of analyzer systems and many others. In addition, psychiatrists work under conditions of high emotional stress, which leads to rapid depletion of the nervous system, the development of a syndrome of professional burnout.